A unidade de perspectivas entre a geografia e a cartografia medievais: paralelos com as artes visuais - Colaço, Douglas (2015)
This paper seeks to recognize, understand and systematize the geographic and cartographic knowledge produced in the Middle Ages. But also sought to relate this knowledge with the visual arts, especially the medieval painting. Thus, the guiding element research has been focused on trying to find and display the similarities and congruences in the production process and construction of the knowledge mentioned hours. Notably by studying the production of medieval knowledge, it is observed that geography was aimed at describing places, spaces and unreal and fanciful beings who existed only in the imagination of the Christian and medieval man, and Cartography was used to represent and locate these places and utopian spaces. This is because the design and representation of space by the medieval scholar were far from scientific accuracy of the classical period as well as the artistic and cultural effervescence lived, especially at the dawn of modernity. Clearly, the great technical and conceptual changes occurred in painting from the XIII century seem to decisively influence the development of modern design and representation of space, characterized mainly by the geometrization of form and movement, but also by the technique of creation the perspective is born originally in the sphere of Renaissance painting to then be appropriated by the Geography and Cartography.